Evaluation of additives and phenological stage on the nutritional value of Tithonia tubiformis silage - Álvarez-García, Cloe Dafne; Sánchez-Valdés, Jair Jesús; Pozo-Leyva, Dixan; Arriaga-Jordán, Carlos Manuel; López-González, Felipe (Ecosistemas y Recursos Agropecuarios, 2023)
The objective was to evaluate Tithonia tubiformis silage with different additives to determine its chemical composition, ruminal fer- mentation parameters and in vitro gas production, two phenological stages (flowering and reproductive) and three additive treatments for the silages were evaluated; control (CTR), molasses (MLZ) and lactic acid bacteria (BAL), through an analysis of variance with a 3x2 factorial experimental design. The variables evaluated were dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), estimated metabolizable energy (eEM), in vitro digestibility of DM (IVDDM), MO (IVDOM) and NDF (IVDNDF), as well as in vitro gas production. Differences (P < 0.05) were found in the chemical composition, in vitro digestibility, eEM and parameters of fermentation kinetics variables between treatments, except for ADF, IVNDF, C1, B, C2 and lag, regarding phenological stages there were differences (P < 0.05) in all variables except for NDF, ADF, A and C1.
Keywords: Animal feed; weed; Tithonia tubiformis